La Loma altitude training center (2007)
La Loma was inaugurated in November 2003 with goal of improving sports in Mexico and providing a first class training facility to athletes from all over the world. Since then, La Loma has had visitors from the United States, Sweden, Germany, United Kingdom, Canada, Costa Rica, France, Spain, Aruba and most of South America in the sports of swimming, track and field, tae kwon do, gymnastics, raquetball, tennis and soccer.